The Potential of Massive Open Online (MOOC) and Its Impact on Future Learning. - Mohd Faiz, Alias (2015)
The Massive Open Online course is a central theme of discussion among academicians, it is however not a new phenomenon. The MOOC concept itself can be traced back to the lifelong learning movement which began in the early 1900's where various group of workers in the UK organised classes to educate themselves to further improve their lives. The movement continued during the industrial age and into the computer era whereupon lifelong learning became a preferred method to reskill oneself and gain more knowledge. In 2002 UNESCO outlined the concept of lifelong learning and referred it as an education targeted to adults outside the student's education systems. The advent of globalisation and the rapid advancement in technology prompted today's society to seek and refine ever more new skills and levels of competency. Malaysia is just one among the many nations who sees lifelong learning as a key proponent to achieving and maintaining a constant pool of human capital. MOOC utilises technology to encourage the use of virtual classrooms around the world as well as capitalising on the large number of eager students. MOOCs are either developed independently by academics or they may be developed via partnership between higher education institutions and third partyonline platforms. They enable students to access high quality academic content, and academics to engage with a much wider audience than before.